Design Of An Information System For Recommendations And Promotion Of Tourist Attractions In East Java - Chalif Fidianata R; Riska Amelia A; Ilfatul Khairani (International Journal of Social Sciences, 2026)
East Java is a province with a wide variety of tourist attractions, including natural, cultural, and man-made attractions spread across various regions. However, information about these attractions is still not well-centralized, so tourists often experience difficulties in finding recommendations for tourist attractions that suit their desires. Based on these problems, this study aims to design a website-based information system for recommendations and promotions of tourist attractions in East Java using the User-Centered Design (UCD) method. The UCD method is used because it emphasizes user involvement in the system design process. The research stages include gathering user needs, designing the system according to user needs, and evaluating the design, which is carried out conceptually without an implementation stage. The result of this study is an information system design that is expected to facilitate tourists in obtaining information and recommendations for tourist attractions, while also helping the process of promoting tourist destinations in East Java more effectively.